Molecular epidemiology of human Borna disease virus 1 infection revisited - Liv Bode; Yujie Guo; Peng Xie (Emerging Microbes and Infections, 2022)
Borna disease virus 1 (BoDV-1) strains attracted public interest by recently reported rare fatal encephalitis cases in Germany. Previously, human BoDV-1 infection was suggested to contribute to psychiatric diseases. Clinical outcomes (encephalitis vs. psychiatric disease) and epidemiology (zoonotic vs. human-to-human transmission) are still controversial. Here, phylogenetic analyses of 18 human and 4 laboratory strains revealed close genomic homologies both in distant geographical regions, and different clinical entities. Single unique amino acid mutations substantiated the authenticity of human strains. No matching was found with those of shrew strains in the same cluster 4, arguing against zoonosis. Opposite epidemiology concepts should be equally considered.